2017
DOI: 10.3233/jpd-171135
|View full text |Cite
|
Sign up to set email alerts
|

Substantia Nigra Neuromelanin as an Imaging Biomarker of Disease Progression in Parkinson’s Disease

Abstract: SN area evaluated by NM-sensitive MRI may be a promising biomarker of nigral degeneration and disease progression in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 40 publications
3
42
2
2
Order By: Relevance
“…Because this observation was apparent in the absence of neurodegeneration of SN neurons, it opened the possibility that NM-MRI measures of NM concentration could be used as a proxy for dopamine function. Second, we developed a voxelwise method that we validated in a cohort of patients with PD, which, consistent with prior work (8,10,(12)(13)(14)(15), exhibited a robust reduction of SN CNR, by showing that our method further revealed a regional pattern of SN signal reduction, consistent with the known topographical pattern of neuronal loss in the disease (27,28). Future studies should directly test this voxelwise method against conventional analysis methods of NM-MRI to determine its ability to enhance classification of PD patients, especially at early or premanifest stages of the illness.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Because this observation was apparent in the absence of neurodegeneration of SN neurons, it opened the possibility that NM-MRI measures of NM concentration could be used as a proxy for dopamine function. Second, we developed a voxelwise method that we validated in a cohort of patients with PD, which, consistent with prior work (8,10,(12)(13)(14)(15), exhibited a robust reduction of SN CNR, by showing that our method further revealed a regional pattern of SN signal reduction, consistent with the known topographical pattern of neuronal loss in the disease (27,28). Future studies should directly test this voxelwise method against conventional analysis methods of NM-MRI to determine its ability to enhance classification of PD patients, especially at early or premanifest stages of the illness.…”
Section: Discussionmentioning
confidence: 66%
“…To test the anatomical specificity of the voxelwise NM-MRI approach, we capitalized on the well-established ability of NM-MRI to detect neurodegeneration in PD and the known topography of cell loss in the illness. Previous PD work has shown decreases in NM concentration (16,17) and in NM-MRI signal in the whole SN (8,15) and lateral regions of bisected SN (12)(13)(14). Histopathological studies of the SN further support a topographical progression of PD pathology that preferentially affects lateral, posterior, and ventral subregions of SN in mild-to-moderate disease stages (27,28).…”
Section: Validation Of Nm-mri As a Proxy Measure Of Dopamine Functionmentioning
confidence: 69%
See 1 more Smart Citation
“…To further detect the changes in the distribution and content of neuromelanin in the SNc, the width and CNR in the lateral, central and medial SNc parts were assessed and consequently it was found that the neuromelanin signal was attenuated in all SNc regions. It was also found that the SNc width was significantly negatively associated with the UPDRS motor score of the clinically most affected side in PD patients, in agreement with the growing clinical evidence which suggested that NM‐MRI changes were associated with disease severity . However, several studies revealed contradictory results .…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Duguid et al [17] observed a reduced width of SN pars compacta in patients with PD using a 1.5T scanner. Since then, several MR studies report a decrease in signal intensity [18][19][20][21][22][23][24][25][26][27][28] and volume or surface reduction [19,21,22,25,26,[28][29][30][31][32][33][34] of the SN in patients with PD. Moreover, discrimination between PD patients and other Parkinsonian syndromes also yields reliable results [29,35,36].…”
Section: Introductionmentioning
confidence: 99%